The political economy of industrial policy in South Africa: the case of downstream beneficiation in the PGM subsector - Ramantsima, Katlego (My University, 2016)
This thesis is centred on the argument that behind the apparent policy consensus around the need for more beneficiation in the mining sector, there are sharp divisions of interest between different class actors and that the implementation of this strategy is limited by the comparative weakness of the state in relation to mining capital. In line with Fine and Rustomjees’ (1996) analysis of the Minerals Energy Complex (MEC), this study explores post-apartheid South Africa’s argument for a developmental state. The MEC is a system of accumulation that has set the pace and tone of the political economy in South Africa. The system evolves through time, depending on the balance and distribution of stakeholders in the mineral sector and has changed into a policy network of participants in the beneficiation policy. Drawing on an analysis of grey literature, policy documents, a series of interviews with individuals from various stakeholders and other relevant groupings with special knowledge on the subject, the research reveals how the various political and economic interests and power relations shape the nature of state intervention through beneficiation in the Platinum Groups Metals (PGM) subsector. The debates around beneficiation are ideological and politicised, dichotomising the state, private capital and labour, ignoring the fact that all stakeholders are an integral part of the MEC. It concludes that South Africa is going through a crisis of state capacity as the state is fragmented, resulting in policy incoherence and strategy misalignment between key departments. This delays development and the quest to pursue successful resource-based industrialisation. Therefore, the idea of a developmental state in post-apartheid South Africa is a contestation.
A research project submitted at the University of the Witwatersrand, Corporate Strategy and Industrial Development (CSID), in partial fulfilment of the Master of Commerce in Development Theory and Policy Degree. March 2015